Anatomical correlation of core muscle activation in different yogic postures - Mrithunjay Rathore; Soumitra Trivedi; Jessy Abraham; Manisha B Sinha (International Journal of Yoga, 2017)
Faulty postures due to sedentary lifestyle cause weakening of core muscles which contributes to increased incidence of musculoskeletal disorders (MSDs). Although a few research studies have quantified the core muscle activity in various yogic exercises used in rehabilitation programs, evidence correlating it to functional anatomy is scarce. Such information is important for exercise prescription when formulating treatment plans for MSDs. Therefore, the objective of this review article is to examine the literature and analyze the muscle activity produced across various yoga postures to determine which type of yoga posture elicits the highest activation for the core muscle in individuals. Literature search was performed using the following electronic databases: Cochrane Library, NCBI, PubMed, Google Scholar, EMBASE, and web of science. The search terms contained: Core muscle activation and yogic posture OR yoga and rehabilitation OR intervention AND Electromyography. Activation of specific core muscle involved asanas which depended on trunk and pelvic movements. Description of specific yogic exercise as they relate to core muscles activation is described. This information should help in planning yogic exercises that challenge the muscle groups without causing loads that may be detrimental to recovery and pain-free movement. Knowledge of activation of muscles in various yogic postures can assist health-care practitioners to make appropriate decisions for the designing of safe and effective evidence-based yoga intervention for MSDs.